If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2(x + 4) = 5(2x + 10) Reorder the terms: 5x + 2(4 + x) = 5(2x + 10) 5x + (4 * 2 + x * 2) = 5(2x + 10) 5x + (8 + 2x) = 5(2x + 10) Reorder the terms: 8 + 5x + 2x = 5(2x + 10) Combine like terms: 5x + 2x = 7x 8 + 7x = 5(2x + 10) Reorder the terms: 8 + 7x = 5(10 + 2x) 8 + 7x = (10 * 5 + 2x * 5) 8 + 7x = (50 + 10x) Solving 8 + 7x = 50 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 8 + 7x + -10x = 50 + 10x + -10x Combine like terms: 7x + -10x = -3x 8 + -3x = 50 + 10x + -10x Combine like terms: 10x + -10x = 0 8 + -3x = 50 + 0 8 + -3x = 50 Add '-8' to each side of the equation. 8 + -8 + -3x = 50 + -8 Combine like terms: 8 + -8 = 0 0 + -3x = 50 + -8 -3x = 50 + -8 Combine like terms: 50 + -8 = 42 -3x = 42 Divide each side by '-3'. x = -14 Simplifying x = -14
| 3(-6-7b)=4(-5b-6) | | 11x+53=7x+55 | | -3-c-6=-3c-6 | | 0.02x-1=2.50 | | x+-10=2y | | -4(2x-3)=-4+6(x-4) | | 2(2r-1)=4r+10 | | 4v^5=4v^3 | | 25x-75=4x-4 | | -7(6x-5)=-42x-35 | | 7(12+x)=7x+84 | | 7(x+2)-2(2x+1)=27 | | 8x+100=9-5x | | 8x-x^2+12=0 | | x+4=2x+10-x | | 5(4x-6)=30 | | -.32(.5x-10.3)=0.6x+9.63 | | 2y=(10+2y)-10 | | -4=2x-3 | | 4(9+x)=48 | | 4(9+x)=4 | | 0.5(m-10)=21 | | 3x+6=8x+16 | | 23.00=4g+3.68 | | 0.2w=0.02 | | 48=3(x+2)(x-4) | | 34-(x+8)=9x-4 | | -4m-24=-4(1+6m) | | 25-v-14=9 | | 19=x-5+x | | 3x=68-x | | 16x^3+32x^6+27x^4= |